THE ROLE OF CENTERS OF VIOLANCE AGAINST WOMEN IN STRUGGLE FOR DOMESTIC VIOLENCE AGAINST WOMEN: ANKARA SIMPLE - İpek Beyza ALTIPARMAK (Fırat University, 2019)
Violence against women is a social problem that is encountered frequently. It no doubt that intellectual transformation is necessary to prevent violence. However, new social policy regulations, support of laws and regulations are necessary in the name of all types of changes and fulfilling lacks. From this point of view, one of the changes is that Ministry of State for Women takes place of Ministry of Family and Social Policies. 6284 numbered regulation of Preventing Violence against Women and Protecting Family comes at the start of the changes that Ministry of Family and Social Policies has done in order to prevent violence against women. It is tried to fulfill the lacks of 4264 numbered regulation and foundation of Centers for Preventing Violence against Women related with violence against women is ruled. Therefore, these centers started to give services as pilot practices like taking supportive and preventive precautions related with violence, gathering application under a single roof, giving guidance and supportive services and ensuring coordination. Centers for Preventing Violence against Women has shown up as centers that aim to ease the process in the name of preventing victimizations caused by the extension of durations in such units as safety, health and psychological support, in a word centers aiming to gather all the units under a single roof. It is desired to have women get over in coordination without their being suffered more and being traumatized again. It is aimed to find out the role of Centers for Preventing Violence against Women in terms of preventing violence against women in the family. Starting from this point of view, interviews were done with the staff of Centers for Preventing Violence against Women in Ankara in 2014. Taking the fastening the duration of intervention and juridical and psychological supports into account, it is thought that the role of Centers for Preventing Violence against Women in preventing violence against women is quite important.